Prospect of Developed Graphite-Resin Electrodes for the Electro-Adsorption Treatment of Water and Wastewater - Aremo, B; Oke, I. A.; Isadare, D. A.; Teniola, O. S.; Akinwole, I. E.; Olorunniwo, O. E.; Akpomejero, T. L. (European Journal of Applied Sciences, 2025)
The relationship between the structure of graphite electrodes and the electro-adsorption treatment process of water purification is not well documented. This paper examines the structure and other properties along with the estimated cost of graphite electrodes. Both non heat-treated graphite-resin electrodes and commercially available heat-treated graphite electrodes were considered. The study characterized the structure of these electrodes and their prospect as materials for electro-adsorption treatment of water and wastewater. The study revealed that there was no significant difference between the selected properties of the developed graphite-resin non heat-treated electrodes and commercial heat-treated graphite electrodes at a 95 % confidence level (F 1,8 = 0.00067 and p = 0.97999). Pores observed on the surfaces of the two electrodes are similar in shape but vary in number and sizes. It was concluded that the two electrodes were similar in structure however the prospect of the developed non heat-treated graphite-resin electrode for electro-adsorption treatment of wastewater is deemed to be higher based on its lower electrical resistance, low cost of production and availability of pores for adsorption.